The static aging effect on the seedless synthesis of different ranges FAU-type zeolite Y at various factors - Al-Jubouri, Sama M. (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
This work investigates generating of pure phase Faujasite-type zeolite Y at the ranges chosen for this study via a static aging step in the absence of seeds synthesis. Nano-sized crystals may result when LUDOX AS-40 is used as a silica source for gel composition of range 6 and the crystallization step may be conducted for a period of 4 to 19 hr at 100 ⁰C. Moreover, large-crystals with high crystallinity pure phase Y zeolite can be obtained at hereinabove conditions but when hydrous sodium metasilicate is used as a silica source. The other selected ranges also offer pure phase Y zeolite at the same controlled conditions.